STRATEGI PENGELOLAAN SAMPAH DALAM PENGEMBANGKAN WISATA EDUKASI DI KOTA BALIKPAPAN PROVINSI KALIMANTAN TIMUR - Kartiwi, Kartiwi (Jurnal Politik Pemerintahan Dharma Praja, 2019)
Waste Management Strategy in Developing Educational Tourism in Balikpapan City, East Kalimantan Province. The research objective was to find out strategies in the development of waste management education tourism carried out by the Office Technical Implementation Unit of Manggar’s Waste Processing Site. In addition, this study also aims to find out the implementing organization and the forms of cooperation carried out in developing waste management education tourism. The method used in this study is action research. The author examines the definition of action research into a field study with data collection techniques in the form of observation, documentation, and interviews. The results of the research findings were analyzed by the SWOT (strength, weakness, opportunities, threats) analysis model. The result is that the strategy for developing the Final Disposal Site in Manggar as a means of production, education, and recreation is based on the master plan of the Department of Landscaping and Funeral Services of Balikpapan City.